Implementasi UU Cipta Kerja dalam Pengembangan UMKM Batik: Studi Kasus di Kampung Batik Turi, Blitar - Olivia Agustina; Eko Adi Susilo; Jalu Sora Wicitra (Perspektif Administrasi Publik dan hukum, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as a key pillar of Indonesia’s national economy, contributing significantly to the Gross Domestic Product (GDP) and employment absorption. Nevertheless, MSME actors continue to face various challenges, including limited access to capital, low digital literacy, and bureaucratic hurdles in business licensing. Law Number 11 of 2020 on Job Creation (UU Cipta Kerja) was introduced as a regulatory breakthrough to address these obstacles by simplifying bureaucracy, offering business incentives, and easing access to digital markets. This study focuses on the implementation of this policy in Kampung Batik Turi, Blitar City, a hub of local wisdom-based MSMEs. The research aims to analyze the local-level application of the Job Creation Law, identify supporting and inhibiting factors, and assess its impact on the growth and independence of batik MSME actors. The findings are expected to offer practical recommendations to strengthen the alignment between national regulation and the actual needs of regional MSMEs, fostering more inclusive and sustainable MSME empowerment.